2016
DOI: 10.1007/s10067-016-3496-2
|View full text |Cite
|
Sign up to set email alerts
|

CD28, CTLA-4 and CCL5 gene polymorphisms in patients with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint destruction caused by infiltrating leukocytes including T cells. An important role in T cell co-stimulation is played by the CD28, as a stimulatory signal transducer and the inhibitory CTLA-4. CCL5 is produced by circulating T cells and plays an active role in the chemotactic activity of T cells in RA. The aim of this study was to examine the associations between polymorphisms within CD28, CTLA-4, and CCL5 genes and RA. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…In our study, rs3087243/G was associated with an increased risk of RA, as has also been reported in Europeans and Asians [27,29]. However, in Mexicans rs3087243/G was associated with decreased RA risk [30], but it showed no association in the Polish population [31]. Two RA GWAS-implicated CTLA4 SNPs (rs11571302, a downstream variant, and rs231735, an upstream variant), which were not covered in our sequencing sample, are also in LD with rs3087243 (Fig 3) [32,33].…”
Section: Plos Onesupporting
confidence: 86%
“…In our study, rs3087243/G was associated with an increased risk of RA, as has also been reported in Europeans and Asians [27,29]. However, in Mexicans rs3087243/G was associated with decreased RA risk [30], but it showed no association in the Polish population [31]. Two RA GWAS-implicated CTLA4 SNPs (rs11571302, a downstream variant, and rs231735, an upstream variant), which were not covered in our sequencing sample, are also in LD with rs3087243 (Fig 3) [32,33].…”
Section: Plos Onesupporting
confidence: 86%
“…It should be noted that studies in autoimmune disease showed controversial results concerning allele and genotype associations with several SNPs as well as other haplotype associations in the CTLA4 and PTPN22 genes [25,27,44,45]. This may be due to ethnic or geographical factors of the studied population.…”
Section: Discussionmentioning
confidence: 92%
“…Apart from the human leukocyte antigen (HLA) locus, a well-known genetic risk factor for RA, numbers of other susceptibility genes and loci have been characterized [6]. Recently, a growing body of non-HLA genetic predisposition studies have been conducted on the association with the risk of RA [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the conclusions which previous reports drew are inconsistent and incomprehensive. Although the association of CTLA-4 genetic polymorphisms and the risk of RA has been assessed in several meta-analyses [21][22][23], some recent studies also described this association in different populations in the past several years [9,15,[24][25][26][27]. Hence these studies should be included to increase statistical power and gain the reliable conclusion.…”
Section: Introductionmentioning
confidence: 99%